2016
DOI: 10.1158/1535-7163.mct-15-0467
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Small Molecule That Overcomes HdmX-Mediated Suppression of p53

Abstract: Inactivation of the p53 tumor suppressor by mutation or overexpression of negative regulators occurs frequently in cancer. Since p53 plays a key role in regulating proliferation or apoptosis in response to DNA damaging chemotherapies, strategies aimed at reactivating p53 are increasingly being sought. Strategies to reactivate wild-type p53 include the use of small molecules capable of releasing wild-type p53 from key, cellular negative regulators, such as Hdm2 and HdmX. Derivatives of the Hdm2 antagonist Nutli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 37 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…Due to advances in understanding the structure and binding mechanisms of p53-MDM2 and p53-MDMX complexes, many inhibitors have been developed to dually inhibit the interactions of p53-MDM2/MDMX, which have been comprehensively discussed in the recent review articles ( 26 29 ). Several specific p53-MDMX binding inhibitors, including, but not limited to, SAH-p53-8 ( 92 ), SJ-172550 ( 94 ), compound B1 ( 96 ), CTX1 ( 97 ), and K-178 ( 98 ) have recently been discovered and shown promising anticancer efficacy and safety profiles in preclinical models in vitro and in vivo ( Table 2 ). Bernal et al have designed and synthesized a stapled p53 helix, named SAH-p53-8 that specifically binds to MDMX with strong affinity ( K D = 2.3 nM) ( 92 ).…”
Section: Mdmx Inhibitors In Preclinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to advances in understanding the structure and binding mechanisms of p53-MDM2 and p53-MDMX complexes, many inhibitors have been developed to dually inhibit the interactions of p53-MDM2/MDMX, which have been comprehensively discussed in the recent review articles ( 26 29 ). Several specific p53-MDMX binding inhibitors, including, but not limited to, SAH-p53-8 ( 92 ), SJ-172550 ( 94 ), compound B1 ( 96 ), CTX1 ( 97 ), and K-178 ( 98 ) have recently been discovered and shown promising anticancer efficacy and safety profiles in preclinical models in vitro and in vivo ( Table 2 ). Bernal et al have designed and synthesized a stapled p53 helix, named SAH-p53-8 that specifically binds to MDMX with strong affinity ( K D = 2.3 nM) ( 92 ).…”
Section: Mdmx Inhibitors In Preclinical Studiesmentioning
confidence: 99%
“…Karan et al have also performed a cell-based screening of a compound library (over 20,000 small molecules) and identified a lead compound CTX1, which induces strong p53-dependent activation in MCF-7 cells expressing a high level of MDMX ( 97 ). Further studies have shown that CTX1 directly binds to MDMX ( K D = 450 nM), prevents the formation of p53-MDMX complex, and activates p53 without causing DNA damage ( 97 ).…”
Section: Mdmx Inhibitors In Preclinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional studies demonstrated XI-006's and XI-011's efficacy in Ewing sarcoma (Pishas et al, 2015) and head and neck cancer cells (Roh, Park, & Kim, 2014), respectively. Subsequent efforts in constructing molecules against MDMX have yielded CTX1, identified by a cell-based screen, which demonstrated efficacy in and synergy with Nutlin against a panel of cancer cells containing wild-type p53 and in a mouse xenograft model using primary human AML cells (Karan et al, 2016). Vassilev et al have also discovered RO-2443 and RO-5963, an indolyl hydantoin series capable of imposing dimerization of MDM2 and MDMX, preventing either of their interactions with p53 (Graves et al, 2012).…”
Section: Small Molecule Wild-type P53 Activatorsmentioning
confidence: 99%